2008
DOI: 10.1210/en.2008-1394
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Peroxisome Proliferator-Activated Receptor (PPAR)-α1 and Truncated PPARα2 as an Adaptive Response to Fasting in the Control of Hepatic Peroxisomal Fatty Acid β-Oxidation in the Hibernating Mammal

Abstract: Seasonal obesity and fasting-associated hibernation are the two major metabolic events governing hepatic lipid metabolism in hibernating mammals. In this process, however, the role of the nuclear receptor known as peroxisome proliferator-activated receptor (PPAR)-alpha has not been elucidated yet. Here we show, as in human, that jerboa (Jaculus orientalis) liver expresses both active wild-type PPARalpha (PPARalpha1wt) and truncated PPARalpha forms and that the PPARalpha1wt to truncated PPARalpha2 ratio, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 62 publications
2
30
0
Order By: Relevance
“…ACADM and ACADL, acting on medium and long chained fatty acids, respectively, however, were not differentially expressed in our study. El Kebbaj et al (35) observed that the activity of ACADM decreased in the livers of hibernating jerboa (Jaculus orientalis) compared with euthermic active animals but increased compared with prehibernating animals. Epperson et al (15) showed that ACADL was significantly overexpressed in the livers of thirteen-lined ground squirrel in Ent versus SA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACADM and ACADL, acting on medium and long chained fatty acids, respectively, however, were not differentially expressed in our study. El Kebbaj et al (35) observed that the activity of ACADM decreased in the livers of hibernating jerboa (Jaculus orientalis) compared with euthermic active animals but increased compared with prehibernating animals. Epperson et al (15) showed that ACADL was significantly overexpressed in the livers of thirteen-lined ground squirrel in Ent versus SA.…”
Section: Discussionmentioning
confidence: 99%
“…The critical threshold (C T ) value is the PCR cycle number where the PCR growth curve crosses a defined threshold in the linear range of the reaction. Gene expression values can be calculated from C T by the formula: 2 35 Ϫ CT . In every real time PCR assay, 18S rRNA was used as the control for significant bias of starting materials across samples.…”
Section: Construction Of Ground Squirrel Proteinmentioning
confidence: 99%
“…PPAR is regulated also by repressive post-trascriptional mechanisms such as -PPAR 2, a A truncated isoform resulting from a posttranslational exon skipping [39] -post-translational modifications such as phosphorylation, [40][41][42].…”
Section: Ppar In Hepatocytesmentioning
confidence: 99%
“…The peroxisome proliferatoractivated receptor (PPAR) family of transcription factors play a key role in lipid metabolism, and controlled regulation of lipid metabolism is integral to mammalian hibernation (Eddy et al 2005b). While PPARgamma and the PPARgamma coactivator (PGC-1alpha) have been shown to respond to hibernation in thirteen-lined ground squirrels (Eddy et al 2005b), PPARα also plays a role in J. orientalis liver during hibernation (El Kebbaj et al 2009). The data showed that jerboa liver expressed an active wild-type form of PPARα (PPARα1wt) and a truncated PPARα (PPARα2tr), and the ratio of wt:tr was differentially regulated during hibernation.…”
Section: Mrna Processing and Stabilitymentioning
confidence: 99%
“…Taken together, mammalian hibernators are subject to substantial transcriptional and posttranscriptional regulation, and various mechanisms have been elucidated to date (Storey and Storey 2004b). For example, work spanning a range of mammalian hibernators has identified epigenetic controls that coordinate the global suppression of transcription (Morin and Storey 2009), the involvement of transcription factors, and their role in achieving a directed cellular response to the various stresses faced as a result of hibernation (Carey et al 2000;Cai et al 2004;Lee et al 2007;Mamady and Storey 2008;Morin et al 2008b;El Kebbaj et al 2009;Tessier and Storey 2012), microRNAs which exert reversible control over translation (Morin et al 2008a;Liu et al 2010;Kornfeld et al 2012), posttranslational modifications which influence the formation of the 48S preinitiation complex (Wu and Storey 2012;Van Breukelen et al 2004), and the disaggregation of polyribosomes during hibernation (Knight et al 2000;Hittel and Storey, 2002;Pan and Van Breukelen 2011).…”
Section: Introductionmentioning
confidence: 99%